2016
DOI: 10.1111/bjop.12198
|View full text |Cite
|
Sign up to set email alerts
|

Life events and functional somatic symptoms: A population study in older adolescents

Abstract: The purpose of this study was to investigate the effect of negative life events on functional somatic symptoms (FSSs) in adolescents, based on data from 957 participants of the population cohort TRacking Adolescents' Individual Lives Survey. Life events experienced between age 16 and age 19 were assessed with the Kendler's Life Stress interview. FSSs at age 19 and age 16 were measured with the Youth and Adult Self-Report. The hypotheses were tested by the use of a latent change model. Life events predicted FSS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
26
0
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(31 citation statements)
references
References 67 publications
2
26
0
2
Order By: Relevance
“…It has consistently been found that the experience of childhood life events is associated with the presence of different types of FSS [ 55 , 56 ]. Earlier studies in this cohort also found an association between sexual abuse and FSS [ 57 ] and childhood adversities and FSS [ 58 ]. Thus, stress and life events might contribute to low grade systemic inflammation in FSS.…”
Section: Discussionsupporting
confidence: 67%
“…It has consistently been found that the experience of childhood life events is associated with the presence of different types of FSS [ 55 , 56 ]. Earlier studies in this cohort also found an association between sexual abuse and FSS [ 57 ] and childhood adversities and FSS [ 58 ]. Thus, stress and life events might contribute to low grade systemic inflammation in FSS.…”
Section: Discussionsupporting
confidence: 67%
“…Acute organic illnesses, stressful work conditions and adverse life events are important precipitating factors for FSS and bodily distress [60,61,62,63,64]. If persisting, these factors together with the effect of predisposing personality aspects and other important psychosocial state and trait characteristics like health anxiety, illness convictions, and avoidance behavior induce a shift to chronification and contribute to the maintenance of the symptoms of FSS and bodily distress.…”
Section: Etiologymentioning
confidence: 99%
“…31 Organic illnesses, stressful work conditions, and adverse life events are important precipitating factors for bodily distress. [32][33][34][35][36] If persisting, these factors and predisposing personality aspects obviously also contribute to the maintenance of the symptoms of bodily distress. Further maintaining factors arise from the often difficult interactions of these patients with the health care system, leading to missed or late correct diagnosis, inappropriate treatments, and frustrations on all sides.…”
Section: Epidemiologymentioning
confidence: 99%